Strategi Komunikasi Dinas Pariwisata Kota Palembang Dalam Membangun Kampung Kreatif - Umi Chalzhum Caniago; Achmad Syarifudin; Muhammad Randicha Hamandiac (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
A communication strategy is needed to produce a communication process that can be understood by the recipient of the information in achieving goals. Therefore, the organization/or company must develop an appropriate communication strategy so that the message conveyed to the target object can be understood well. The research was conducted to analyze the performance of the Tourism Department in implementing the strategy of the Creative Village, especially in the communication aspect, because there are still many villages that do not participate in Creative Village activities, this is due to the lack of understanding of the village community about what, the purpose, why and the elements of the Creative Village itself. Therefore, the researcher wrote the thesis entitled "Tourism Service Communication Strategy in Building Creative Villages". The aim of the research is to find out the communication strategy of the Palembang City Tourism Office, as well as to find out the supporting and inhibiting factors in implementing this communication strategy. The research method used is qualitative with a descriptive approach, field research type and data collection techniques using participant observation, interviews and documentation. Results of research on the communication strategy of the Palembang City Tourism Office. Using communication strategy stages, namely: 1. Getting to know the audience, 2. Developing messages, 3. Methods used, 4. Selection and use of media. This is also inseparable from the existence of supporting and inhibiting factors. And in accordance with the results of research on the communication strategy of the Palembang City Tourism Office in building Creative Villages, it has been carried out well, but there are still some village communities in Palembang City District who do not understand what the Village is about, the purpose, why and the elements of the Creative Village so that choose not to take part in Creative Village activities.